TRAINING PROGRAMME TO HOTELS BARRANQUILLA FOR ATTENTION TO PEOPLE WITH DISABILITIES - De La Hoz Montenegro, Carmela Isabel
This project analyzes the existing problems in the Barranquilla’s hotels regarding the level of training of workers in the accommodation sector respect to the care of people with disabilities. The development of a complementary training program focused on the care and service, that should be provided to people with disabilities in hotels, derives from the inconveniences that have been presented with these clients when using hotel services. Barranquilla city is growing in its hotel capacity, besides being an epicenter of sports events for people with disabilities, for example, the wheelchair tennis tournament held annually in this city; therefore, it is essential to have qualified personnel to meet your needs and achieve the total satisfaction of these clients. According to its scope, it responds to a descriptive inquiry. To the date the characterization of hotels in Barranquilla has been carried out, the checklists have been applied to establish the architectural accessibility and the level of training of the workers, and then design the complementary training program focused on the care of persons with disabilities.